8+7r=-8(r-1)

Simple and best practice solution for 8+7r=-8(r-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8+7r=-8(r-1) equation:


Simplifying
8 + 7r = -8(r + -1)

Reorder the terms:
8 + 7r = -8(-1 + r)
8 + 7r = (-1 * -8 + r * -8)
8 + 7r = (8 + -8r)

Add '-8' to each side of the equation.
8 + -8 + 7r = 8 + -8 + -8r

Combine like terms: 8 + -8 = 0
0 + 7r = 8 + -8 + -8r
7r = 8 + -8 + -8r

Combine like terms: 8 + -8 = 0
7r = 0 + -8r
7r = -8r

Solving
7r = -8r

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '8r' to each side of the equation.
7r + 8r = -8r + 8r

Combine like terms: 7r + 8r = 15r
15r = -8r + 8r

Combine like terms: -8r + 8r = 0
15r = 0

Divide each side by '15'.
r = 0

Simplifying
r = 0

See similar equations:

| -6v-11=4(-2v+6)-1 | | 4.5x-1.5=12 | | -12+4p=-p+3p | | 0=x^4-2x^3-4x^2+2x+3 | | (4x^3+8x)(x^2-3)=0 | | 830+y=520 | | 7x^2=1028 | | x^4+2*x^2*y^2+y^4=2 | | (x^2+y^2)=x^3 | | x^2+y^2=3 | | -4x-8=3x-7 | | 2/7/4/6 | | 40+2x=48 | | 45/27=40/x | | -4/9-1/6 | | 0=-32t^2+64t | | 0=-32t^2+64y | | 1-.75= | | 9-2x=6-c | | (6x+16)*(2x)=(2x+18)*(4x) | | -5/4*2/3 | | 4x+5x+40=180 | | y=6(x+3) | | y=6(x+3)4 | | p/3-3p/8=4 | | 5(2k+4)=6+8k | | 6.3+3.8= | | 39+3a=-8(2a+3)+6 | | 1-x/5=2x+1 | | 21c-18=36 | | 17.50+4s=53.50 | | X+7-1+3=1-3x+3x |

Equations solver categories